Kemampuan Menyusun Recount Text Menggunakan Media Gambar Berseri Pada Siswa Kelas X Teknik Pemesinan - Lalang Eka Supriatna (Jurnal Pendidikan dan Sastra Inggris, 2021)
English lessons are very important for students, but most vocational students think that these subjects, especially in Compiling Recount Text material, are boring and very difficult. The purpose of this research is to improve student learning outcomes in compiling recount text using serial picture media. This research is a class action research with a total of 32 students in class X Mechanical Engineering at SMK Negeri 1 Cibeber, Lebak Regency, for the 2020/2021 academic year, all of whom are male. Based on the analysis in each cycle, it shows that the use of serial picture media can improve student learning outcomes in recount text material. This can be seen from the increase in the average student score and the large increase in the percentage of students who achieve the KKM score in each cycle.